An investigation into the role of non-metallic inclusions in cleavage fracture of medium carbon pearlitic steels for high-speed railway wheel. (January 2022) - Zhou, Shi-tong; Li, Zhao-dong; Jiang, Lu; Wang, Xin; Xu, Pian; Ma, Yu-xi; Yan, Yu-ping; Yang, Cai-fu; Yong, Qi-long
Graphical abstract: Highlights: The effects of non-metallic inclusions on the cleavage fracture and toughness of medium carbon pearlitic wheel steels were investigated. Spherical oxides promote cleavage fracture by indirectly inducing crack initiation (do not themselves act as crack nuclei, but cause crack initiation at the surrounding steel matrix). Elongated sulfides do not promote the initiation of cleavage fracture in the longitudinal direction and can also break the continuous propagation of cleavage cracks by sulfide cracking or debonding. In the case of cleavage-dominated fracture, by refining oxide inclusions or increasing sulfur content the longitudinal fracture toughness can be improved. Abstract: Non-metallic inclusions are often considered to be detrimental to the toughness of steels. Here, we found that, in a cleavage-dominated fracture mode, the toughness, particularly the room temperature fracture toughness of pearlitic wheel steel can be improved by refining oxide inclusions or by increasing sulfur content. The roles of these inclusions in crack initiation and propagation were carefully investigated. Intriguingly, no spherical oxides or elongated sulfides were found to be the direct sources of cracks in the cleavage fracture within both Charpy V-notch and compact tension specimens. Cleavage cracks were found to be originated only from the steel matrix. Based on the theory of cleavage fracture and direct microscopic observations, the mechanisms were proposed for understanding the inclusion-toughness relations: (i) the oxide inclusions could indirectly induce crack initiation by enhancing local stress concentration, therefore promoting cleavage fracture and being detrimental to the toughness; (ii) in addition to enveloping the oxides to reduce the local stress concentration, the sulfide inclusions could also break the continuous propagation of cleavage cracks in the longitudinal direction by sulfide cracking or debonding, which released the stress concentration at the crack tip and enhanced the plastic work of fracture, thereby being beneficial to the toughness improvement.